Catalan numbers with applications - Koshy, Thomas (New York ; Oxford : Oxford University Press, 2009)
This title presents a comprehensive introduction to Catalan numbers. They crop up in chess, computer programming and even train tracks. In addition to lucid descriptions of the mathematics and history behind Catalan numbers, the author includes short biographies of the prominent mathematicians who have worked with the numbers.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Catalan numbers (Mathematics)